Durability Studies of Remanufacturable Components for Extended Life Cycle / Ammer Ezhar Mohd Razalli ... [et al.] - Mohd Razalli, Ammer Ezhar; Abd. Wahab, Dzuraidah; Mohd Ihsan, Ahmad Kamal Ariffin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The concept of remanufacturing that requires automotive components to enter a new life cycle in 'as new' condition is certainly a challenge to the remanufacturers. A remanufacturable component has to be designed for durability to ensure that its functional performance is retained after reaching its end of life. To date, there is no systematic approach in ensuring the durability of remanufacturable components to ensure that they are fit for use in their subsequent life cycles apart from visual inspection and testing after the reassembly process. Therefore, it is necessary to conduct an evaluation on the damage and life cycle of remanufacturable components. In this study, an automotive air conditioning compressor was used as a case example. The function of a compressor is to compress refrigerant inside the air conditioning system. After years of usage, the internal parts of the compressor such as bearing, o-rings and seal tend to be damaged and become unusable. However, its casing known as the core has the potential to be reused for several life cycles through remanufacturing. A simulation test on the compressor comprising static and fatigue tests are carried out and the results show that the compressor casing has the ability to be remanufactured since there are only minimal damage and a large number of life cycles. Findings from the study will assist manufacturers in understanding the importance of designing for durability for purposes of recovery strategies such as remanufacturing, which serve as a new demand in the automotive industry